1979
DOI: 10.3109/10731197909117579
|View full text |Cite
|
Sign up to set email alerts
|

Implant Failures in Orthopaedic Surgery

Abstract: Common orthopaedic implant failures are reviewed in the areas of total joint replacement and fracture fixation. In particular total hip and total knee arthroplasty, intertrochanteric hip fractures and long bone fractures are discussed. Excessive motion of implant bone interfaces, stress concentrations within the implant and stress shielding of bone are implicated in implant failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1982
1982
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…They also calculated the stress distributions in the natural bone and found that the Ritter-Grunert prosthesis produced a stress distribution much closer to the physiological state than did the conventional prosthesis. This failure site has also been described by Harris and Tarr (1979).…”
Section: Results Of Beam Theory Applied To Total Hip Replacementsmentioning
confidence: 53%
“…They also calculated the stress distributions in the natural bone and found that the Ritter-Grunert prosthesis produced a stress distribution much closer to the physiological state than did the conventional prosthesis. This failure site has also been described by Harris and Tarr (1979).…”
Section: Results Of Beam Theory Applied To Total Hip Replacementsmentioning
confidence: 53%
“…The most popular and structures made of polylactic acid (PLA) and Poly-DL-lacticco-glycolic acid (PLAGA) are being used and are likely to replace metal implants in the near future (Agrawal et al, 1999;Lu et al, 2000). These bioabsorbable products have several advantages over metal implants: (1) no stress-shielding effect, (2) no need for removal after surgery, and (3) no metallic corrosion (Kawahara et al, 1980;Rice et al, 1978;Pilliar, 2003;Harris and Tarr, 1978). However, each of these has some shortcomings that restrict its applications.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, it has been suggested that surgical technique and implants are possible causative factors for nonunion. Weil et al 25) have attracted attention by advocating that delays in healing may be caused by a decrease in load transfer due to stress shielding 31) . For this reason, early ambulation has been recently recommended, and the wider use of load sharing devices has been suggested 6) .…”
Section: Discussionmentioning
confidence: 99%